2012
DOI: 10.1111/j.1468-0084.2012.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Punishing the Foreigner: Implicit Discrimination in the Premier League Based on Oppositional Identity*

Abstract: We present the first empirical study to reveal the presence of implicit discrimination in a non-experimental setting. By using a large dataset of in-match data in the English Premier League, we show that white referees award significantly more yellow cards against non-white players of oppositional identity. We argue that this is the result of implicit discrimination by showing that this discriminatory behaviour: (i) increases in how rushed the referee is before making a decision, and (ii) it increases in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Goddard and Wilson (2008) reported an advantage for black players in career progression and retention in English professional football. Frick (2008) found that in professional football in Germany, the players from South America enjoyed a higher premium than their colleagues did; yet, Gallo et al (2013) found evidence of discrimination by referees against non-white players in the English Premier League. Bullough and Mills (2014) reported a decline over a twenty-year period in the appearance of English players in the English Premier League pointing to diminishing opportunities for indigenous players.…”
Section: Partial Mediation Model Of Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Goddard and Wilson (2008) reported an advantage for black players in career progression and retention in English professional football. Frick (2008) found that in professional football in Germany, the players from South America enjoyed a higher premium than their colleagues did; yet, Gallo et al (2013) found evidence of discrimination by referees against non-white players in the English Premier League. Bullough and Mills (2014) reported a decline over a twenty-year period in the appearance of English players in the English Premier League pointing to diminishing opportunities for indigenous players.…”
Section: Partial Mediation Model Of Performancementioning
confidence: 99%
“…For example, racial discrimination in European football leagues has been highlighted repeatedly, both in terms of fan behaviour and institutionalized barriers (Bradbury, 2013;Kilvington, 2013;Cleland and Cashmore, 2014;Dixon et al, 2016). However, over the years, many scholars have investigated player discrimination on multiple fronts using various indicators, and have obtained results both affirming and negating the existence of discrimination (Reilly and Witt, 1995;Szymanski, 2000, Pedace, 2008Frick, 2008;Gallo et al, 2013;Bullough and Mills, 2014;Posso et al, 2016). Yet, most studies have not focused on salary and the relationship between pay and performance as the crux for evaluating disparities.…”
Section: Introductionmentioning
confidence: 99%
“…10 In Equation (1), the performance of a firm (or team) in a given season is explained by the skills of its workers (or players), the ability of its manager (or coach) to exploit the worker's talent, and the variable of interest. The pioneering work of Rottenberg (1956) supports the underlying logic of the equation discrimination against colored players even though they have been playing in England in significant numbers for at least three decades (see for instance Gallo, Grund, and Reade 2013;Palacios-Huerta 2014, chapter 11;or Silberzahn and Uhlmann 2015).…”
Section: The Modelmentioning
confidence: 94%
“…Indeed Earley and Mosakowski (2000) conclude that moderately heterogeneous groups show a low level of team identity. Gallo, Grund, and Reade (2013) building on the concept of oppositional identity derived by Akerlof and Kranton (2000), empirically evaluate whether referees in the EPL tend to discriminate against oppositional identical players implicitly. Exploiting the fact that the referees in their dataset were all born in the United Kingdom, they find that referees tend to book players with which they would not identify as they naturally do with White players.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation